Stigma Functionality and Fertility Are Reduced by Heat and Drought Co-stress in Wheat - Fábián, Attila; Sáfrán, Eszter; Szabó-Eitel, Gabriella; Barnabás, Beáta; Jäger, Katalin (Frontiers in Plant Science, 2019)
As a consequence of climate change, unpredictable extremely hot and dry periods are becoming more frequent during the early stages of reproductive development in wheat (Triticum aestivum L.). Pollen sterility has long been known as a major determinant of fertility loss under high temperature and water scarcity, but it will be demonstrated here that this is not the exclusive cause and that damage to female reproductive organs also contributes to losses of fertility and production. Changes in the phenology, morphology and anatomy of female reproductive cells and organs, in the ROS and RNS generation of stigmatic papilla cells, and in fertility and yield components in response to simultaneous high temperature and drought at gametogenesis were studied in two wheat genotypes with contrasting stress responses. The combination of high temperature (32/24°C) and total water withdrawal for 5 days at gametogenesis altered the phenology of the plants, reduced pollen viability, modified the morphology and the anatomy of the pistils, enhanced the generation of ROS and RNS, intensified lipid peroxidation and decreased the NO production of stigmatic papilla cells, all leading to reduced fertility and to production loss in the sensitive genotype, depending on the position of the floret on the spike. Reduced functionality of female and male reproductive parts accounted for 34% and 65%, respectively, of the total generative cell- and organ-triggered fertility loss.